2019
DOI: 10.18662/rrem/190
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Methods of Formation of Military and Special Competence in Future Border Guard Officers in the Continuing Education Process

Abstract: Military and special competence in border guard officers is essential for their successful professional activities. The purpose of the article is to distinguish the relevant organizational methods for the formation of military and special competence as a necessary condition for enhancement of efficiency of the educational process and describe their implementation in the continuing education process. To achieve the purpose the following methods were used: theoretical methods (bibliographical method, comparative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Digital tools can collect and analyze the data on cadets' performance, engagement, and learning outcomes (Xu et al, 2022). Moreover, digitalization often reflects the tools and technologies used during professional or combat activities (Torichnyi & Bhinder, 2019). Using these tools in the educational process, future military engineers can gain valuable skills and experiences that will prepare them to carry out professional tasks efficiently.…”
Section: Digitalization In Military Engineering Education: Practices ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Digital tools can collect and analyze the data on cadets' performance, engagement, and learning outcomes (Xu et al, 2022). Moreover, digitalization often reflects the tools and technologies used during professional or combat activities (Torichnyi & Bhinder, 2019). Using these tools in the educational process, future military engineers can gain valuable skills and experiences that will prepare them to carry out professional tasks efficiently.…”
Section: Digitalization In Military Engineering Education: Practices ...mentioning
confidence: 99%
“…Additionally, according to Galynska and Bilous (2022), using e-learning demonstrated that digital tools are capable of delivering education to the areas wrecked by war. The training of future military engineers usually involves various digital tools, platforms, and resources to increase their learning experience (Torichnyi & Bhinder, 2019). Today, many engineering programs use simulations and virtual laboratories (Maistrenko et al, 2020), artificial intelligence (AI) (Hadlington et al, 2023), online learning platforms, and learning management systems (LMS) (Bularca et al, 2024), computer-aided software, gamification (Kozubtsov & Nesterov, 2024), and data analysis tools (Kaluzny, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Starchuk (2011) outlined the structure of future officers' readiness to combat activities, O. Torichnyi and N. Bhinder (2019) specified organizational methods of formation of military and special competence of future officers. V. Ulich (2007) studied future officers' management readiness, S. Ishchenko (2014) and Yu.…”
Section: Literature Reviewmentioning
confidence: 99%